Study Effect of Infection With Treponema Palladum at the Level of Antibodies and Some Blood Parameters and its Relationship With Blood Factions (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study was conducted on 30   patients and 20 healthy people to determine the influences of infected with Treponema pallidum on levels of IgM , IgA, IgG  ,Complement4 ,complement 3 and some Blood parameters in infected with T. Pallidum also relation disease with blood factions  in compared with healthy group who have visited Al-Sadder Medical City and Al-Hakeem Hospital in Al- Najaf governorate during the period from August 2014 till February 2015 in Al-Sadder Medical City Laboratories .The results showed significant increase (P